Analisis Strategi Diferensiasi dalam Meningkatkan Positioning pada Warung Kopi di Rantau Prapat - Muhammad Ilham Arif; Ade Parlaungan Nasution; Junita Lubis (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze differentiation strategies in improving positioning at Rantauprapat coffee shops. The number of samples is 96 respondents, namely coffee shop owners in Rantauprapat. This study uses validity tests, reliability tests, classical assumption tests, multiple linear regression tests, t tests, F tests, and coefficients of determination using SPSS. The study was conducted to examine how independent variables influence dependent variables and the percentage level of influence of research variables by distributing research questionnaires to respondents and conducting tests. The results of the study indicate that product differentiation, service differentiation and image differentiation have a positive and significant effect on positioning both partially and simultaneously. It can be seen from the results of the determination coefficient in the Adjusted R Square column, which is 0.791. This value means that positioning can be explained by product differentiation, service differentiation and image differentiation by 79.1%. While the rest is influenced by other variables not examined in this study.